2021
DOI: 10.3390/polym13040534
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Presence of Disulphide Bonds in Aromatic or Aliphatic Dicarboxylic Acid Hardeners Used to Produce Reprocessable Epoxidized Thermosets

Abstract: The design of polymers from renewable resources with recycling potential comes from economic and environmental problems. This work focused on the impact of disulphide bonds in the dicarboxylic acids reactions with three epoxidized vegetable oils (EVOs). For the first time, the comparison between aromatic vs. aliphatic dicarboxylic acids, containing or not S–S bonds with EVOs was discussed and evaluated by dynamic scanning calorimetry. The obtained thermosets showed reprocessability, by the dual dynamic exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The temperature dependence of stress relaxation (Figure 1, right) is accurately captured by an Arrhenius-type model, with an activation energy of 70 kJ/mol, a value comparable to that of previously reported vitrimers based on disulfide exchange. 8,9,17,18 As can be seen from the same figure, the curves are truncated when the relaxations practically come to a halt (i.e., E/E 0 ≅ 0.5), The linear regression is performed after normalizing these truncated curves. The linear Arrhenius plot is given in Figure S4.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature dependence of stress relaxation (Figure 1, right) is accurately captured by an Arrhenius-type model, with an activation energy of 70 kJ/mol, a value comparable to that of previously reported vitrimers based on disulfide exchange. 8,9,17,18 As can be seen from the same figure, the curves are truncated when the relaxations practically come to a halt (i.e., E/E 0 ≅ 0.5), The linear regression is performed after normalizing these truncated curves. The linear Arrhenius plot is given in Figure S4.…”
mentioning
confidence: 99%
“…This stress relaxation property is the most commonly studied manifestation of dynamic networks. Recently, Chen et al reported such a material wherein the two exchange reactions can be simultaneously and synergistically triggered, leading to very fast stress relaxation Later, Mauro and Mija reported similar disulfide-ester dually relaxing polyepoxide materials with particular focus on material properties . Similar epoxy-based vitrimers have also been prepared using amine curing agents .…”
mentioning
confidence: 99%
“…Via external stimuli such as UV irradiation, heat, and chemical methods, these dynamic and/or reversible chemical bonds have the ability to rearrange their topologies. It is also reported that such disulfide linkages can highly increase the reactivity of the aliphatics, aromatics, or diacids used for copolymerization, resulting in higher- T g materials . In another interesting study, mixing aliphatic–aromatic and acid–amine hardeners with epoxidized camelina oil resulted in a possible lower curing temperature .…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that such disulfide linkages can highly increase the reactivity of the aliphatics, aromatics, or diacids used for copolymerization, resulting in higher-T g materials. 32 In another interesting study, mixing aliphatic−aromatic and acid−amine hardeners with epoxidized camelina oil resulted in a possible lower curing temperature. 33 Rapid stress relaxation was another attribute reported with enhanced mechanical properties when dynamic polymer networks and hydroxyl functionalized silica reinforcement were used.…”
Section: Introductionmentioning
confidence: 99%
“…T g and cross-link density were higher than which in epoxy vitrimers without disulfide bonds and the recyclability of the network was demonstrated. 33 Similarly, Zeng et al used 3,3′-thiodipropionic acid (DTDPA) to crosslink rosin derivative and obtained epoxy vitrimer. The relaxation time at 170 °C was 3.3 times than that of singleester vitrimer, and the recovery rate of tensile strength after reprocessing reached 90.6%.…”
Section: Introductionmentioning
confidence: 99%